Reninoma: a rare cause of arterial hypertension - Pina, Rui (2004)
Juxtaglomerular cell tumours, also called reninomas, are benign and rare causes of secondary high blood pressure.The authors present a case of a 19-year-old woman, admitted to the Coimbra University Hospitals Department of Medicine, suffering from high blood pressure of recent onset. Laboratory fi ndings revealed a decrease in serum potassium and an increased plasma renin and plasma aldosterone level. The abdominal magnetic resonance scan revealed a mass in the right kidney, in its middle portion. The right renal artery angiography confi rmed the topographic localization, as well as the poor vascularization of the mass.In the presence of these fi ndings, the patient was proposed for surgery, which was successfully performed without any complications (a parenquimal-sparing excision of the tumour was performed). The histological study of the tissue excised revealed a reninoma.